(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Nutraceuticals integration within pharmacy practice produces a fundamental transformation that brings large chances together with various obstacles. Food-derived nutraceuticals have become increasingly popular because healthcare providers recognize their abilities to stop and help control different chronic medical conditions. Pharmacy practice is undergoing a transformation which extends pharmacist roles beyond medication dispensing to lead active prevention of disease while promoting wellness for patients.